Comparative Analysis of Mesenchymal Stromal Cells Biological Properties. (28th March 2013) - De Luca, Angela; Verardi, Rosanna; Neva, Arabella; Benzoni, Patrizia; Crescini, Elisabetta; Xia, Er; Almici, Camillo; Calza, Stefano; Dell'Era, Patrizia
Abstract : The stromal progenitors of mesodermal cells, mesenchymal stromal cells (MSCs), are a heterogeneous population of plastic adherent fibroblast-like cells with extensive proliferative capacity and differentiation potential. Human MSCs have now been isolated from various tissues including bone marrow, muscle, skin, and adipose tissue, the latter being one of the most suitable cell sources for cell therapy, because of its easy accessibility, minimal morbidity, and abundance of cells. Bone marrow and subcutaneous or visceral adipose tissue samples were collected, digested with collagenase if needed, and seeded in Iscove's medium containing 5% human platelet lysate. Nonadherent cells were removed after 2-3 days and the medium was replaced twice a week. Confluent adherent cells were detached, expanded, and analyzed for several biological properties such as morphology, immunophenotype, growth rate, senescence, clonogenicity, differentiation capacity, immunosuppression, and secretion of angiogenic factors. The results show significant differences between lines derived from subcutaneous fat compared to those derived from visceral fat, such as the higher proliferation rate of the first and the strong induction of angiogenesis of the latter. We are convinced that the identification of the peculiarities of MSCs isolated from different tissues will lead to their more accurate use in cell therapy.